Analisis Bibliometrik: Penelitian Tentang Implementasi Sistem Manajemen Keselamatan Ketenagalistrikan (SMK2) di Indonesia (2014–2024) - Hendro Kristanto; Rohenda Rohenda (SENTRI: Jurnal Riset Ilmiah, 2025)
This study looks at the research landscape on Electricity Safety Management Systems (SMK2) in Indonesia from 2014 to 2024 using bibliometric analysis. The research is imperative due to SMK2's pivotal function as a national regulatory framework (ESDM Ministerial Regulation No. 10 of 2021) for guaranteeing operational safety in the power sector, highlighting the inadequate comprehension of academic focus and collaboration trends. The clear goals are to chart the amount, collaboration networks, thematic evolution, and global positioning of Indonesian research on SMK2. A bibliometric method was used to look at and show data from Scopus, SINTA, and Google Scholar using VOSviewer. Out of 615 qualifying publications, only 125 (20.3%) come from Indonesia. Co-authorship analysis shows that Chinese researchers make up the majority of five collaborative clusters, while Indonesian researchers are not present in the core network. Co-occurrence analysis finds five main thematic clusters, with SMK2 on the edge and not strongly linked to any of them. The global research trend indicates a transition from traditional safety measures to energy digitalization. The main contribution of the study is a detailed empirical map that shows how Indonesia is not very well connected to the global SMK2 research ecosystem. The practical implication is the clear need for strategic actions to improve collaboration on domestic research, combine SMK2 studies with digital energy themes, and help Indonesian researchers publish more internationally to support evidence-based and sustainable SMK2 implementation.